Przemyt marihuany jako źródło patologii oraz zagrożenie bezpieczeństwa społecznego i ekonomicznego w Polsce - Olech, Aleksander Ksawery (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2017)
Drug trafficking is a threat to both social security and economic development. Ensuring internal security involves eliminating threats, avoiding them and reducing the probability of their occurrence in the future. Marijuana, being uncontrolled, unregulated and harmful to people, is transported between countries illegally. This is a problem that has existed for dozens of years around the world, and since the beginning of the twentieth century it is also noticeable in Poland. The activity of international criminal groups forces the security services to react and cooperate at the European level. The article aims to show that cannabis is nowadays a significant problem for society and a major challenge for law enforcement. Drugs are the subject of many debates and deliberations of psychologists, politicians, therapists, teachers, functionaries and environmental activists. Although Polish law prohibits the cultivation and distribution of cannabis, the number of users increases from year to year. To ensure security in Poland, organizations have been established that should counteract the smuggling. The reaction of the security services should be compatible with the existing negative situation in the field of counteracting drug threats.